Carbon Monoxide is an Inhibitor of HIF Prolyl Hydroxylase Domain 2. (29th June 2021) - Mbenza, Naasson M.; Nasarudin, Nawal; Vadakkedath, Praveen G.; Patel, Kamal; Ismail, A. Z.; Hanif, Muhammad; Wright, L. James; Sarojini, Vijayalekshmi; Hartinger, Christian G.; Leung, Ivanhoe K. H.
Abstract: Hypoxia‐inducible factor prolyl hydroxylase domain 2 (PHD2) is an important oxygen sensor in animals. By using the CO‐releasing molecule‐2 (CORM‐2) as an in situ CO donor, we demonstrate that CO is an inhibitor of PHD2. This report provides further evidence about the emerging role of CO in oxygen sensing and homeostasis. Abstract : Carbon monoxide (CO) is an endogenously produced gasotransmitter that is involved in a range of physiological roles including the stabilisation of hypoxia‐inducible factor (HIF), a transcription factor that regulates oxygen homeostasis. Herein, by using CO‐releasing molecule‐2 as a CO donor, we show that CO is an inhibitor of HIF PHD2, one of the most important oxygen sensing enzymes in humans that regulates HIF stability at the protein level.